the DEMONSTRASI PRODUK AL-NAZHIFAH DENGAN AKAD ISTISHNA’ SEBAGAI UPAYA PENCEGAHAN STUNTING PADA MASYARAKAT LUMAJANG - Siti Aisyah; Nabila Nailil Amalia; Muhaiminah Darajat; Hafizh Idri Purbajati; Muhammad Zamroni (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
The purpose of this study is to describe the al-nazhifah product with the istishna' contract to prevent the increase in stunting rates, especially in Lumajang district. The method used is descriptive qualitative with documentation, observation and interview data collection. Data analysis used in this study is source triangulation. The results of this study are that the Fastabiqul Khoirot Lumajang Sharia Savings and Loans Cooperative has a superior product with the istishna' contract called al-nazhifah. Many Lumajang residents do not have good sanitation infrastructure, so this financial institution not only provides financing, but also a technical team that can help with consultation and construction of sanitation facilities. If more and more families use Al Nazifah to get access to safe sanitation. This good collaboration will lead to improved health and welfare for the Lumajang community.